2013
DOI: 10.2105/ajph.2013.301335
|View full text |Cite
|
Sign up to set email alerts
|

Homelessness and Money Mismanagement in Iraq and Afghanistan Veterans

Abstract: Objectives We examined the empirical link between money mismanagement and subsequent homelessness among veterans. Methods We used a random sample of Afghanistan/Iraq era veterans from the National Post-Deployment Adjustment Survey in 2009–2011. Results Veterans were randomly selected from a roster of all U.S. military service members in Operation Iraqi Freedom or Operation Enduring Freedom who were separated from active duty or in the Reserves/National Guard. Veterans (n = 1090) from 50 states and all mili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…VA disability compensation has been found to be protective against homelessness (12), but high rates of substance use disorders have been found among homeless veterans (13), suggesting that homeless veterans who receive VA disability compensation may use it to support addictive habits resulting in their homelessness. Many homeless veterans also have problems managing their money, and money mismanagement has been identified as a potential target for intervention in this population (14).…”
mentioning
confidence: 99%
“…VA disability compensation has been found to be protective against homelessness (12), but high rates of substance use disorders have been found among homeless veterans (13), suggesting that homeless veterans who receive VA disability compensation may use it to support addictive habits resulting in their homelessness. Many homeless veterans also have problems managing their money, and money mismanagement has been identified as a potential target for intervention in this population (14).…”
mentioning
confidence: 99%
“…In one study of psychiatric inpatients at four VA hospitals, clinicians indicated that 27 patients (11% of the sample) were in need of a payee (Marc I. Rosen et al, 2002). Other studies, not focused specifically on payee assignment, have described frequent difficulty managing their funds among people with mental health conditions (Elbogen, Sullivan, Wolfe, Wagner, & Beckham, 2013; Marson et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Because people with SMI are often poor, with no financial cushion, the consequences of money mismanagement can be severe, and include increased probability of homelessness (Conrad et al 1998; Elbogen et al 2013), depression (Weiser et al 2006), higher psychiatric symptom severity (Conrad et al 2006b), more missed medical appointments (Weiser et al 2006), reduced overall functioning (Black et al 2008; Conrad et al 2006b), and family conflict (Angell et al 2007; Elbogen et al 2007). Despite the importance of money mismanagement in people with SMI, little is known about characteristics of people most prone to mismanage their funds.…”
mentioning
confidence: 99%